Electrophysiological Studies into the Safety of the Anti-diarrheal Drug Clotrimazole during Oral Rehydration Therapy. - Willem S Lexmond; Paul A Rufo; Edda Fiebiger; Wayne I Lencer (Public Library of Science (PLoS), 2015)
Morbidity and mortality from acute diarrheal disease remains high, particularly in developing countries and in cases of natural or man-made disasters. Previous work has shown that the small molecule clotrimazole inhibits intestinal Cl- secretion by blocking both cyclic nucleotide- and Ca(2+)-gated K(+) channels, implicating its use in the treatment of diarrhea of diverse etiologies. Clotrimazole, however, might also inhibit transporters that mediate the inwardly directed electrochemical potential for Na(+)-dependent solute absorption, which would undermine its clinical application. Here we test this possibility by examining the effects of clotrimazole on Na(+)-coupled glucose uptake.Short-circuit currents (Isc) following administration of glucose and secretagogues were studied in clotrimazole-treated jejunal sections of mouse intestine mounted in Ussing chambers.Treatment of small intestinal tissue with clotrimazole inhibited the Cl- secretory currents that resulted from challenge with the cAMP-agonist vasoactive intestinal peptide (VIP) or Ca(2+)-agonist carbachol in a dose-dependent fashion. A dose of 30 μM was effective in significantly reducing the Isc response to VIP and carbachol by 50% and 72%, respectively. At this dose, uptake of glucose was only marginally affected (decreased by 14%, p = 0.37). There was no measurable effect on SGLT1-mediated sugar transport, as uptake of SGLT1-restricted 3-O-methyl glucose was equivalent between clotrimazole-treated and untreated tissue (98% vs. 100%, p = 0.90).Treatment of intestinal tissue with clotrimazole significantly reduced secretory responses caused by both cAMP- and Ca(2+)-dependent agonists as expected, but did not affect Na(+)-coupled glucose absorption. Clotrimazole could thus be used in conjunction with oral rehydration solution as a low-cost, auxiliary treatment of acute secretory diarrheas.